2022
DOI: 10.2196/39532
|View full text |Cite
|
Sign up to set email alerts
|

Wearables for Measuring Health Effects of Climate Change–Induced Weather Extremes: Scoping Review

Abstract: Background Although climate change is one of the biggest global health threats, individual-level and short-term data on direct exposure and health impacts are still scarce. Wearable electronic devices (wearables) present a potential solution to this research gap. Wearables have become widely accepted in various areas of health research for ecological momentary assessment, and some studies have used wearables in the field of climate change and health. However, these studies vary in study design, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…First, researchers and funding agencies should pursue large-scale cooperative projects leveraging repeated person-level sleep measures (including, but not limited to personal sensing technologies) and longitudinal study designs across larger, and more globally diverse populations, and for longer periods of unobtrusive observation. 87 The geographic distribution of studies conducted so far does not cover the global distribution of the human population (Figures 2, 3B). Drawing on these timeseries data, researchers should explicitly control for time-invariant between-individual differences to identify within-person temperature-sleep responses.…”
Section: Discussionmentioning
confidence: 99%
“…First, researchers and funding agencies should pursue large-scale cooperative projects leveraging repeated person-level sleep measures (including, but not limited to personal sensing technologies) and longitudinal study designs across larger, and more globally diverse populations, and for longer periods of unobtrusive observation. 87 The geographic distribution of studies conducted so far does not cover the global distribution of the human population (Figures 2, 3B). Drawing on these timeseries data, researchers should explicitly control for time-invariant between-individual differences to identify within-person temperature-sleep responses.…”
Section: Discussionmentioning
confidence: 99%
“…50 Despite the evidence that various environmental characteristics have diverse impacts on human health, personal urban environmental exposure monitoring appears limited. 51 PUFP C200, a personal portable particle counter smart wearable was combined with the NEATVIBE wear TM (Noise Exposure, Activity-Time, and Vibration) wearable. Preliminary field test findings using two laboratory-validated tools that measure personal-scale exposures and noise with high spatiotemporal resolution.…”
Section: Monitoring Environment Exposurementioning
confidence: 99%
“…If children and adolescents have difficulty expressing their emotions or interpreting high stress, physiological indicators such as temperature, heart, and respiratory metrics may be useful. Koch et al (2022) conducted a scoping review and found 53 studies that used wearables to assess the impact of extreme climate-related weather events, almost 10% of which were on children under the age of 18.…”
Section: Technologymentioning
confidence: 99%